2017
DOI: 10.2474/trol.12.94
|View full text |Cite
|
Sign up to set email alerts
|

Loss Reduction of Rolling Bearings for Automobile

Abstract: The role of rolling bearings is to support rotational motion with low friction. Although the friction is low in rolling bearings, it does not mean that friction does not occur at all. Many rolling bearings are used in automobiles. Therefore, if it is possible to reduce the friction loss in the rolling bearings, it can contribute to reducing the fuel consumption of the automobile. In this paper, we introduce representative techniques for reducing the friction in automotive bearings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…T.Sada and his colleagues examined friction loss reduction of ball bearings [4]. Ł.Gorycki and his colleagues analyzed the impact of the cage type on the frictional moment of ball bearings and showed that the type of cage used in ball bearings has a significant impact on the frictional moment [5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…T.Sada and his colleagues examined friction loss reduction of ball bearings [4]. Ł.Gorycki and his colleagues analyzed the impact of the cage type on the frictional moment of ball bearings and showed that the type of cage used in ball bearings has a significant impact on the frictional moment [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As friction force increases, ball bearing life decreases [4]. Theoretically, we have 2 main equations to calculate the friction force [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rolling bearings have seen fast progress in manufacturing and design over the last decade, with broad usage in a variety of sectors [1][2][3][4][5]. It is widely accepted that the application of rolling bearings has advantages in terms of reducing cost, size, weight, and friction.…”
Section: Introductionmentioning
confidence: 99%